Dasar Pertimbangan Hakim dalam Pengembalian Anak Pelaku Pencurian dengan Pemberatan kepada Orang Tua : (Studi Putusan 20/Pid.Sus-Anak/2023/PN Kla) - Hernandy Taufiqurohman; Erna Dewi; Fristia Berdian Tamza (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research is motivated by the decision of the Kalianda District Court Number 20/Pid.Sus-Anak/2023/PN Kla which imposed a sentence to return the child who committed the crime of theft with aggravation to the parents. The purpose of this study is to analyze the basis for the judge's considerations legally, philosophically, and sociologically in making this decision. The research method uses a normative legal approach with a study of court decision documents and analysis of related literature. The findings show that legally, the judge considered the provisions in the Juvenile Criminal Justice System Law which prioritizes the principles of restorative justice and child protection. Philosophically, considerations are based on the child's right to grow and develop in a family environment and the importance of recovery, not retaliation. Sociologically, the judge pays attention to the family's condition, the child's social environment, and the recommendations of the Community Guidance Officer who assesses that the child can still be fostered under the supervision of parents. The implications of this study emphasize the importance of a multidimensional approach in handling children's cases, so that court decisions not only fulfill legal aspects, but also support the growth and development and social reintegration of children in society.